Relationship Level Of Education And Knowledge With The Incidence Of Dermatitis In The CommunityAt Puskesmas Patek, Aceh Jaya District - Hafni Zahara; Putri Raisah; Taufiq Karma; Yesi Yuliana (Sean Institute, 2023)
Skin disease is the most workers' disease after bone and muscle disease. Occupational contact dermatitis ranks first in occupational skin diseases, 80% are irritant contact dermatitis and the remaining 20% ​​are allergic contact dermatitis. In general, this study aims to see whether there is a relationship between the level of education and knowledge with the incidence of contact dermatitis in the community in the working area of ​​the Patek Public Health Center, Aceh Jaya district, with a total population of 198 people. This study used a quantitative research type with a cross sectional approach. The population in this study was 198 people with a sample of 67 people using a purposive sampling technique in taking the sample. Statistical analysis using chi-square test. The results showed that 24 (35.8%) respondents had junior high school education, 33 (49.3%) had high school education, and 10 (14.9%) undergraduate education. Based on the statistical test with the chi-square test, it was obtained that the p value = 0.455 (> 0.05) then Ha is accepted, which means that there is no relationship between education and the incidence of dermatitis. While the 25 respondents who had high knowledge there were 11 people (16.4%) who had allergic contact dermatitis and 14 people (20.9%) who had irritant contact dermatitis. While the 42 respondents who had low knowledge, there were 14 people (20.9%) who had allergic contact dermatitis and 28 people (41.8%) who had irritant contact dermatitis. Based on statistical tests with the chi-square test, it was obtained that p value = 0.383 (> 0.05) so Ha was accepted, which means that there is no relationship between education and the incidence of dermatitis.